13 Hemosuccus Pancreaticus Due to a Large Pseudoaneurysm in Gastroduodenal Artery, a Life Threatening Complication. (11th January 2018) - Heidarian, Amin; Gupta, Raavi
Abstract: Hemosuccus pancreaticus is bleeding in the duodenum through pancreatic duct. In 3%-10% cases of chronic pancreatitis, release of pancreatic enzymes cause digestion of the wall of arteries resulting in hematoma in the pancreatic parenchyma or pseudoaneurysm. Rupture of this pseudoaneurysm is an uncommon but life-threatening complication and accounts for less than 1% of cases of gastrointestinal bleeding. Hemosuccus pancreaticus in the setting of chronic pancreatitis is usually from splenic artery. Hemorrhage from other abdominal arteries such as gastroduodenal artery is very rare. Here, we present a case of large pseudoaneurysm originating in the gastroduodenal artery, which proved terminal due to massive gastrointestinal hemorrhage. A 70-year-old man with past medical history of hypertension, diabetes mellitus, and chronic ethanol dependence presented with lethargy and black tarry stools and hemoglobin of 8.7 g/dL. Abdominal CT scan showed a large vascular mass in the head/neck of the pancreas. Gastrointestinal (GI) endoscopy confirmed bleeding from the ampulla of Vater. Interventional radiology studies showed that the vascular mass is originating from one of the branches of celiac trunk. As surgery was contraindicated due to low hemoglobin, coil embolization was tried twice, which failed to stop the bleeding. Multiple blood transfusions were given however due to failure to stop bleeding from the artery, the patient succumbed to exsanguination. Autopsy showed a 6.5 cm peripancreatic pseudoaneurysm originating from the gastroduodenal artery connecting to the main pancreatic duct. The pancreas was severely atrophic and calcified. There was altered blood in GI tract distal to the ampulla of Vater. This is a rare case of hemosuccus pancreaticus in a patient with history of chronic pancreatitis, which was fatal in this patient.